2016
DOI: 10.1007/s12011-016-0858-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Selenium Against Cyclophosphamide-Induced Cardiotoxicity in Rats

Abstract: The objective of this study is to evaluate the possible protective effects of selenium (Se) against cyclophosphamide (CP)-induced acute cardiotoxicity in rats. A total of 42 male Spraque-Dawley rats were divided into six groups (n = 7). Rats in the first group were served as control. Rats in the second group received CP (150 mg/kg) at the sixth day of experiment. Animals in the third and fourth groups were treated with only 0.5 and 1 mg/kg Se respectively for six consecutive days. Rats in the fifth and sixth g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
3
23
0
1
Order By: Relevance
“…Gunes et al [72] Male Sprague Dawley rats Animals received respective selenium (Se) doses (0.5 or 1 mg/kg) for 6 days and then a single dose of CP administered on the sixth day. On day 7, the animals were sacrificed.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Gunes et al [72] Male Sprague Dawley rats Animals received respective selenium (Se) doses (0.5 or 1 mg/kg) for 6 days and then a single dose of CP administered on the sixth day. On day 7, the animals were sacrificed.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…Other pharmacological inductions of heart damage used doxorubicin to induce cardiomyopathy [64] and cyclophosphamide to induce cardiotoxicity [63]. Both doxorubicin and cyclophosphamide are anticancer drugs with cardiotoxicity as their major adverse effect [72,73] and are commonly used to induce cardiotoxicity and heart failure (HF) in animal models [74][75][76][77]. Hypercholesterolemia is commonly induced by high fat or cholesterol diet.…”
Section: Animal Studiesmentioning
confidence: 99%
“…In a study by Demirci et al, authors showed that se-lenium treatment might have benefi cial effects in oxidative stress, infl ammation and apoptosis (51). Also, it is known that selenium has cardioprotective effects against toxic elements, xenobiotics and viral infections (19).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we wanted to evaluate the effect of bevacizumab on calcium signaling, apoptosis and oxidative stress in cardiomyocytes and we wanted to investigate the modulator role of selenium (as an important cardioprotective antioxidant) in bevacizumab induced cardiotoxicity (19).…”
Section: Introductionmentioning
confidence: 99%